Unmaking the global sweatshop : health and safety of the world's garment workers - Prentice, Rebecca; Neve, Geert de (Pennsylvania studies in human rights., 2017)
Unmaking the Global Sweatshop gathers the work of leading anthropologists and ethnographers studying the global garment industry's impact on workers' well-being and examines the relationship between the politics of labor and initiatives to protect workers' health and safety.